Dietary exposure to aflatoxin B1, ochratoxin A and fuminisins of adults in Lao Cai province, Viet Nam: A total dietary study approach. (December 2016) - Huong, Bui Thi Mai; Tuyen, Le Danh; Tuan, Do Huu; Brimer, Leon; Dalsgaard, Anders
Abstract: Aflatoxins, fumonisins and ochratoxin A that contaminate various agricultural commodities are considered of significant toxicity and potent human carcinogens. This study took a total dietary study approach and estimated the dietary exposure of these mycotoxins for adults living in Lao Cai province, Vietnam. A total of 42 composite food samples representing 1134 individual food samples were prepared according to normal household practices and analysed for the three mycotoxins. Results showed that the dietary exposure to aflatoxin B1 (39.4 ng/kg bw/day) and ochratoxin A (18.7 ng/kg bw/day) were much higher than recommended provisional tolerable daily intake (PTDI) values mainly due to contaminated cereals and meat. The exposure to total fumonisins (1400 ng/kg bw/day) was typically lower than the PTDI value (2000 ng/kg bw/day). The estimated risk of liver cancer associated with exposure to aflatoxin B1 was 2.7 cases/100, 000 person/year. Margin of exposure (MOE) of renal cancer linked to ochratoxin A and liver cancer associated with fumonisins were 1124 and 1954, respectively indicating risk levels of public health concern. Further studies are needed to evaluate the efficiency of technical solutions which could reduce mycotoxin contamination as well as to determine the health effects of the co-exposure to different types of mycotoxins. Highlights: Aflatoxin B1 and ochratoxin A exposures were higher for adults in Lao Cai than the provisional tolerable daily intake. Contaminated cereals and meat were main sources of mycotoxins. The estimated risk of liver cancer associated with exposure to aflatoxin B1 was 2.7 cases/100, 000 person/year. Margin of exposure for cancer linked to ochratoxin A and fumonisins indicates risk levels of public health concern.